2009
DOI: 10.1590/s0034-89102009000900009
|View full text |Cite
|
Sign up to set email alerts
|

Prática de atividades físicas e fatores associados em adultos, Brasil, 2006

Abstract: OBJETIVO: Estimar a prevalência da prática de atividades físicas por adultos e sua associação com fatores sociodemográficos e ambientais. MÉTODOS: Foram utilizados dados do Sistema de Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico coletados em 2006. Os 54.369 adultos entrevistados residiam em domicílios com linha telefônica fixa nas capitais brasileiras e Distrito Federal. A prática de atividades físicas foi considerada nos domínios do lazer, trabalho, atividade domést… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
55
3
49

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 22 publications
11
55
3
49
Order By: Relevance
“…4 Additionally, the results of this study showed that people invited to practice physical activity are more likely to be active in leisure.…”
Section: Discussionmentioning
confidence: 68%
“…4 Additionally, the results of this study showed that people invited to practice physical activity are more likely to be active in leisure.…”
Section: Discussionmentioning
confidence: 68%
“…16 Physical activity and nutrition were evaluated with a questionnaire used in the Vigitel system. 9,11 Those who did no physical activity in their free time, or had done so less than once a week in the three months previous to the interview were deemed inactive; those who had done some kind of physical activity in their free time at least once a week over the same period were deemed active. 9 nutrition was evaluated according to regular consumption of fruit and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Those who did no physical activity in their free time, or had done so less than once a week in the three months previous to the interview were deemed inactive; those who had done some kind of physical activity in their free time at least once a week over the same period were deemed active. 9 nutrition was evaluated according to regular consumption of fruit and vegetables. 11 The anthropometric measurements; body mass, height and waist circumference were evaluated according to standardised procedures.…”
Section: Introductionmentioning
confidence: 99%
“…En estudios para evaluar los niveles de actividad física de la población adulta a nivel global, son evidentes las desigualdades por sexo, nivel socioeconómico y nivel educativo (9)(10)(11)(12). Las prevalencias de inactividad física en el dominio de tiempo libre son mayores en las mujeres (33,9 Vs. 27,9 %) y en la población con menor nivel socioeconómico y educativo (9)(10)(11)(12).…”
unclassified
“…Las prevalencias de inactividad física en el dominio de tiempo libre son mayores en las mujeres (33,9 Vs. 27,9 %) y en la población con menor nivel socioeconómico y educativo (9)(10)(11)(12). Estas desigualdades son aún más evidentes en los países en desarrollo (9).…”
unclassified